PENGARUH PSIKOLOGI REKAYASA TATA RUANG KERJA TERHADAP MOTIVASI KERJA TENAGA KEPENDIDIKAN UNIVERSITAS TEKNOLOGI SUMBAWA - Zakiya Hanifa, Lana; Hasri Rosandi, Fitra (Wakil Rektor 3, Direktorat Pengabdian kepada Masyarakat dan Publikasi, Universitas Teknologi Sumbawa, 2021)
Sumbawa University of Technology certainly has goals that must be achieved. The study of the psychology of engineering workspace in order to increase the work motivation of educational staff is expected to open the door to achieve this goal. This research was conducted to determine the effect of the psychology of engineering workspace on the work motivation of education staff at the Sumbawa University of Technology by using descriptive quantitative research. The sampling of this research used random sampling technique, obtained as many as 40 samples of education staff from the Sumbawa University of Technology. The research data was obtained using the psychology scale of work layout engineering and work motivation scale. The results showed that there was an influence of the psychology of work layout engineering on the work motivation of the Sumbawa Technology University Education Staff with a significance value (Sig.) of 0.035 (<0.05), obtained R value is 0.334 and R Square value is 0.112. Where the value of R shows the value of the correlation coefficient or the value of the psychological relationship between work layout engineering and work motivation of 0.334, based on the correlation coefficient table, this value is included in the low category, so that the contribution of the influence (R Square) of workspace engineering psychology in increasing work motivation education is only 11.2%, while the other 88.8% is influenced by other variables that are not examined in this study.